ARID1A loss-of-function induces CpG island methylator phenotype. (28th April 2022) - Yamada, Harumi; Takeshima, Hideyuki; Fujiki, Ryoji; Yamashita, Satoshi; Sekine, Shigeki; Ando, Takayuki; Hattori, Naoko; Okabe, Atsushi; Yoshikawa, Takaki; Obama, Kazutaka; Katai, Hitoshi; Kaneda, Atsushi; et al.
Abstract: The CpG island methylator phenotype (CIMP) is associated with prognosis and drug sensitivity in multiple cancer types. In gastric cancer, the CIMP is closely associated with Epstein-Barr virus (EBV) infection and AT-rich interactive domain 1A ( ARID1A ) mutations, a component of the SWI/SNF chromatin remodeling complex. However, the involvement of SWI/SNF defects in CIMP induction has been unclear. In this study, we demonstrate a causal role of ARID1A loss-of-function in CIMP induction. Mutations of SWI/SNF components, especially ARID1A, was associated with the CIMP, as well as EBV infection, in gastric cancers, and also in uterine endometrial and colorectal cancers, which are not affected by EBV infection. Genome-wide DNA methylation analysis showed that ARID1A knockout (KO) in cultured 293FT cells and gastric epithelial cells, GES1, induced aberrant DNA methylation of a substantial number of CpG sites. DNA methylation was induced at genomic regions with high levels of pre-existing histone H3 lysine 27 trimethylation (H3K27me3) and those with acquired H3K27me3 by ARID1A KO. These results showed that the ARID1A mutation induced aberrant DNA methylation, and this is likely to be one of the potential mechanisms of CIMP induction. Highlights: ● ARID1A mutation is associated with the CIMP, as well as EBV infection, in gastric cancers, and also uterine endometrial and colorectal cancers. ● ARID1A loss-of-function is causally involved in aberrant DNA methylation induction. ● Aberrant DNA methylation is induced at genomic regions with pre-existing and acquired H3K27me3 by ARID1A KO.